(untitled) (Journal of Chemical Engineering, 2010)
The objectives of this work were to monitor and quantify the airborne particles (PM10 and PM2.5) and to predict the influence of human and natural activities on their ambient concentrations. Samples of Air-borne Particulate Matter (APM) in the size range 0-2.5 μm (PM2.5) and 0-10 μm (PM10) were collected simultaneously using two MiniVol portable air samplers at Mohakhali and Farmgate area in Dhaka city. At Mohakhali effective sampling duration was from May 16 to May 23, 2004 and at Farmgate from June 6 to June 13, 2004. Continuous seven day monitoring was carried out to find the effect of meteorology, traffic load and other anthropogenic activities on ambient Particulate Matter (PM) pollution level. Weekday and weekend average traffic number was evaluated by field technicians at both sampling sites. These sites are regarded heavily polluted because of the proximity of major roadways. Daily and weekly average concentrations of PM10 and PM2.5 at Mohakhali were found higher than USEPA and Bangladesh 24-hrs average guideline values but at Farmgate the concentrations were within the guideline values. Average proportions of PM2.5 in PM10 were found higher at Farmgate than that at Mohakhali. Journal of Chemical Engineering Vol.ChE 24 2006 61-67